Effects of interprofessional education for medical and nursing students: enablers, barriers and expectations for optimizing future interprofessional collaboration – a qualitative study - Sabine Homeyer and Wolgang Hoffmann and Peter Hingst and Roman F. Oppermann and Adina Dreier-Wolfgramm (BMC nursing, 2018)
Background